Zinc selenide (ZnSe) nanoparticle coated with green seaweed (Ulva fasciata) hydroalcoholic extract as an anti-leishmanial compound on Leishmania major. - Zahra Atef; Fatemeh Livani; Faramarz Koohsar; Roghiyeh Faridnia; Ganesh Yadagiri; Hamed Kalani (PLoS ONE)
This study focused on evaluating the effectiveness of zinc selenide nanoparticles coated with green seaweed (Ulva fasciata) (ZnSe-Uf) against Leishmania major (L. major) in light of increasing drug resistance in the treatment of cutaneous leishmaniasis and the growing necessity for new therapeutic options. Key characteristics of ZnSe-Uf, including shape, size, functional groups, zeta potential, and polydispersity index, were analyzed in detail. The study investigated the effects of different concentrations of ZnSe-Uf compared to meglumine antimoniate (MA; used as the control), on both the promastigote and amastigote forms of L. major, calculating the selectivity index (SI) for each. Analysis revealed that the dominant functional group in ZnSe-Uf was C-H stretching, attributed to polysaccharides, lipids, and proteins. The size of ZnSe-Uf ranged from 228.2-242.8 nm (P = 0.37), with a polydispersity index of 0.31-0.33 (P = 0.85), and a zeta potential ranging from -35.6 mV to -57.9 mV (P = 0.07) over a period of 90 days. The lethal concentration 50 (LC50) for ZnSe-Uf was 7.61 μg/mL, while for MA it was 17.37 μg/mL on promastigote (P = 0.03). On amastigote, the LC50 was 24.3 μg/mL for ZnSe-Uf and 12.3 μg/mL for MA (P = 0.04). The SI was 27.55 for ZnSe-Uf and 41.26 for MA (P = 0.02). The lower LC50 for MA on amastigote indicated its better effectiveness on L. major compared to ZnSe-Uf, suggesting that ZnSe-Uf may have a lower ability to concentrate in macrophages compared to MA. However, ZnSe-Uf still showed anti-leishmanial activity and was non-toxic to macrophages (SI > 10), indicating the need for further investigation on animal models.